Fortalecimiento de las habilidades blandas para el mejoramiento de la convivencia escolar a través de un OVA en estudiantes de 5° de primaria del Colegio Francisco Javier Matiz (2022)
The Francisco Javier Matiz School presents problems of coexistence, which is why this research sought to strengthen soft skills for the improvement of school coexistence in 5th grade. A qualitative type of research was used, with a quasi-experimental design, which sought to determine the progress between soft skills (HB) and school coexistence. In addition, a virtual learning object (VLO) was designed and implemented to contribute to the appropriation of these soft skills. We worked with a non-probabilistic sample of 30 students, divided into a control group and an experimental group. The information collected allowed concluding that the soft skills are related to and significantly influence the improvement of school coexistence of the students who received the intervention with the OVA in relation to the control group. Finally, the development of the soft skills, under the guidance of the OVA, not only strengthened them, but also enriched the integral and coexistence formation of the students.